The exterior of Shiva Temple (Temple 1) - Temples of India Project Team (Jio Institute, 2024)
A view of the Shiva Temple (Temple 1) in Cluster 1 from the south, showing the vertical axis of the temple. It has a well-defined vedibandha (basal mouldings) comprising different mouldings such as the khura, kumbha (pot-shaped), antarapatta (recesses between mouldings), and kapotapalika (cyma recta moulding). It has a simple and plain jangha (wall), ornately carved varandika (moulded parapet), and shikhara (superstructure) which is in a dilapidated condition. The intact part of the shikhara reveals the brickwork marked with the chaitya (dormer window) arch design.